(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Data is the main asset of the modern companies and their businesses. Typically, it is stored in the data-base. Every database system has to be capable of responding to information requests from users, which is queries of the process. Encryption mechanisms are required, which give the capability to the query over the encrypted data-base and permit the optimization of data encryption and decryption. However, applying encryption algorithms on Encrypted database then challenge arises that the efficiency of the system degrades on deploying encryption algorithm on the runtime. Therefore, this paper presents most of the recent works that have been conducted on the query preprocessing of encrypted database and analyzes them to clarify the performance analysis, based on different performance metrics in each related work.